THE ANALYSIS OF GENERIC STRUCTURE OF DESCRIPTIVE TEXTS PRODUCED BY COLLEGE STUDENTS - Achmad Hilal Madjdi; Atik Rokhayani (Universitas Muria Kudus, 2022)
Writing is a challenging skill for some English students. Before writing, students must consider the genre. A text type is genre. It's not easy to apply genre theory in writing. The students must comprehend the text's genre, general organization, and lexico-grammatical features. They have lots of ideas but can't put them into a nice writing. This is a big issue for some EFL students. This study examined the impact of genre choice and generic structure on students' writing. The researchers studied the English Class of the Psychology Department of Universitas Muria Kudus. This study is descriptive qualitative. The descriptive qualitative examines the study of students' writings based on genre choice and generic structure. This study was conducted in English class at Universitas Muria Kudus at Psychology Department. Based on the research findings, students' descriptive texts consisted of a generic structure of identification and description. A person's introduction is described in identification. A person is described in a description. Identification and description were well used by all students. Thus, the students consistently used generic structure in their writings. However, there were issues with punctuation, diction, and meaning. This research may help English Education Department, especially students who need to better their texts and think about generic organization and challenges while writing.